1996
DOI: 10.1007/bf00049340
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a maize ribosomal P2 protein cDNA and phylogenetic analysis of the P1/P2 family of ribosomal proteins

Abstract: The nucleotide sequence of a full-length ribosomal P2 protein cDNA from maize was determined and used for a sequence comparison with the P2 and P1 proteins from other organisms. The integration of these data into a phylogenetic tree shows that the P proteins separated into the subspecies P1 and P2 before the eukaryotic kingdoms including plants developed from their ancestor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Mitochondrial and chloroplastic L12 proteins are structural homologs of eubacterial L12 (22,23) and are therefore distinct from the cytosolic 12 kDa P-proteins. Phylogenetic analyses (24,25) support the hypothesis that a single ancestral L12 gene may have duplicated and subsequently diverged very early in the eukaryotic lineage to produce the P1 and P2 proteins found in contemporary eukaryotes (20,21). …”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Mitochondrial and chloroplastic L12 proteins are structural homologs of eubacterial L12 (22,23) and are therefore distinct from the cytosolic 12 kDa P-proteins. Phylogenetic analyses (24,25) support the hypothesis that a single ancestral L12 gene may have duplicated and subsequently diverged very early in the eukaryotic lineage to produce the P1 and P2 proteins found in contemporary eukaryotes (20,21). …”
mentioning
confidence: 68%
“…Evolutionary relatedness between P1 and P2 type proteins was reported (24,25). Alignment of P1 and P2 with the colinear archaebacterial homolog, L12, indicated that P1 and P2 form distinct, monophyletic groups (25).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, scarce information is available regarding ARPs; however, it is known that their molecular masses range between 12 and 17 kDa, as in most eukaryotes, and their cDNA deduced amino acid sequences indicate a similar structure to their animal and yeast counterparts (10)(11)(12). P1 and P2 proteins have been isolated from maize tissues (13) and their cDNA sequences reported (14,15), including a P3 cDNA expressed in roots during anoxia (16).…”
mentioning
confidence: 99%
“…Comparison of the chiton coding sequence with corresponding P2 family members from the brine shrimp (Artemia salina, Amons et al, 1979), yeast (S. pombe, Beltrame and Bianchi, 1990), Drosophila (Qian et al, 1987), maize (Zea mays, Goddemeier et al, 1996), and rat (Lin et al, 1982) gave sequence identities of 53%, 53%, 50%, 63%, and 64%, respectively. The P2 protein is involved in protein elongation occurring at the ribosome (Qian et al, 1987) and may also function as an intracellular iron-binding protein (Furukawa et al, 1992).…”
Section: S Ribosomal Proteins From Chitonmentioning
confidence: 99%
“…S27 protein family members are about 90 amino acids in size and contain zinc-finger motifs that are involved in RNA-DNA binding, probably serve to stabilize ribosomes, and may influence gene transcription (Wool et al, 1990). Acidic P proteins consist of representatives of P1 and P2 families (P, phospho) that share a common progenitor sequence (Goddemeier et al, 1996). The P proteins are important contributors to the elongation phase of protein synthesis (Qian et al, 1987).…”
Section: Introductionmentioning
confidence: 99%